Construction of a human-wildlife spatial interaction index in the Three-River Source Region, China. (October 2021) - Ma, Bingran; Xie, Yuxi; Zhang, Tongzuo; Zeng, Weihua; Xue, Yinglan
Highlights: A human-wildlife spatial interaction index was proposed. The average level of human-wildlife interaction in the study area was low. Higher potential human-wildlife interaction occurred in areas with roads and rails. Abstract: In the context of today's rapid economic development and increasingly strict ecological protection, interactions between humans and wildlife will intensify. Therefore, we need to identify the spatial distribution of such interactions and to take measures to mitigate possible negative interactions. Using the Three-Rivers Source Region as a case study, we combined species habitat suitability, species feeding habits, species conservation levels and human impact intensity to construct a "human-wildlife spatial interaction index" (HWSII) to evaluate the intensity of human-wildlife spatial interactions. The overall level of HWSII was relatively low in the Three-River Source Region. Higher potential human-wildlife interactions occurred in areas with roads and railways. Areas of relatively high interactions between carnivores and livestock were mainly located in the southern part of the study area, and those with relatively high interactions between herbivores and livestock appeared in the western and eastern parts. Managers in these areas should consider mitigation measures. Although developed for a specific region of China, the 'human-wildlife spatial interaction index' could have application in other areas of the world for setting a baseline reference to identify areas with the potential for high levels of human-wildlife interactions and pinpoint places where potential negative interactions can be mitigated.